The Concept of Justice in Inheritance Distribution According to Fiqh Mawaris - Indra Komara Candra (EL-IQTISHAD: Journal of Economics, Business and Sharia Studies, 2026)
The distribution of inheritance in Islamic jurisprudence is governed by legal principles concerning heirs, providing comprehensive guidance on the rights of heirs as articulated in the Qur'an and Hadith. This study aims to critically examine the concept of equity in inheritance distribution as portrayed by fiqh mawaris. Equity within this framework is not viewed as absolute parity but rather as proportional justice that considers the social and economic obligations placed on each heir. For instance, the difference in shares allotted to men relative to women is based on the subsistence responsibilities that men bear within the family structure. However, this interpretation of justice often faces scrutiny due to perceptions of inconsistency with contemporary gender equality principles. Consequently, modern ijtihad and instruments such as wills or endowments (waqf) may serve as viable alternatives to achieve a form of justice more aligned with societal developments, while still adhering to the foundational principles of sharia. The study’s findings indicate that the concept of justice in inheritance distribution under fiqh mawaris can be adapted while upholding the principle of maslahah to ensure balance and fairness in family relations.